Archaeology in Asia Minor - Mellink, Machteld J.
spez. Palaeolithic Sites: Küçükçekmece, Karain, Urfa – Neolithic, Chalcolithic and Bronze Age Sites: Kültepe, Boğazköy, Alaca Hüyük, Karahüyük, Çatalhüyük, Suberde, Can Hasan, Fasıllar, Acemhüyük, Pulur, Urfa-Diyarbakır Area, Gendere Cave Near Arsameia, Malatya, Gaziantep, Tilmen Hüyük, Gedikli Hüyük, Amanus Passes, Yalıncak-Kocumbeli, Ilıca-Ayaş, Karataš-Semayük, Bodrum-Müsgebi, Iasos, Manisa-Kula, Marmara-Thrace – Iron Age and Classical Sites: Altıntepe, Van-Toprakkale, Çavuştepe, Ernis, Adılcevaz, Patnos, Ani, Karatepe, Boğazköy and other Classical Sites.